2017
DOI: 10.1097/md.0000000000006313
|View full text |Cite
|
Sign up to set email alerts
|

Using a pedicle pectoralis major musculocutaneous flap in head and neck reconstruction after modified radical mastectomy

Abstract: Rationale:A pedicle pectoralis major musculocutaneous (PMMC) flap is one of the strategies for head and neck reconstruction. Seldom studies reported the case in which the skin area of previous modified radical mastectomy (MRM) had been used as a PMMC flap in head and neck reconstruction.Patient concerns:An 84-year-old female who had suffered from left breast cancer and undergone a left modified radical mastectomy (MRM) more than 20 years earlier.Diagnoses:She had squamous cell carcinoma of the tongue and had u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…The pectoralis major muscle flap was first described by Pickrell in 1947 as a turnover flap in chest wall reconstruction [1] but the pedicle pectoralis major myocutaneous (PMMC) flap based on the thoracoacromial artery procedure was originally developed by Dr Ariyan in 1979 and has been widely used in the reconstruction of head and neck defects [2][3][4][5].On human anatomy the pectoralis major has a clavicular head, a sternocostal head, and an abdominal portion [1,6]. It was shown that the skin obtains its blood supply through the underlying muscle [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The pectoralis major muscle flap was first described by Pickrell in 1947 as a turnover flap in chest wall reconstruction [1] but the pedicle pectoralis major myocutaneous (PMMC) flap based on the thoracoacromial artery procedure was originally developed by Dr Ariyan in 1979 and has been widely used in the reconstruction of head and neck defects [2][3][4][5].On human anatomy the pectoralis major has a clavicular head, a sternocostal head, and an abdominal portion [1,6]. It was shown that the skin obtains its blood supply through the underlying muscle [7].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the pectoralis major myofascial (PMMF) and PMMC, are by far the most employed techniques [2]. The PMMF is consisting in the use of pectoralis major muscle alone with overlying fascia without the skin paddle [4]. While PMMC is more suitable for reconstruction involving skin defects, the PMMF variant better complies with mucosal defects [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selain itu, dibandingkan free flap prosedur ini lebih singkat dan tidak memerlukan pemantauan intensif post operasi. 10 Kelemahan pectoralis major myocutaneous flap adalah kemungkinan sirkulasi darah tidak konsisten yang dapat menyebabkan nekrosis flap sebagian atau total. Nekrosis kulit merupakan komplikasi yang banyak ditemukan; angka kejadian nekrosis kulit antara 7% sampai 27%.…”
Section: Diskusiunclassified